(untitled) - Moravcik, Lubomir (Doprava a spoje, 2011)
Natural gas founded, thanks to its properties, its place, not only as raw material in chemical industry, or in power industry (power station), in households (heating, cooking and water heating), but also as a transport fuel. The main advantages of natural gas, as fuel for road vehicles, are environmental, economic, operational and safety benefits.